Pengembangan Media Permainan Monobiling Dalam Efikasi Diri Akademik Siswa Di SMA Negeri 15 Surabaya - Ardiansyah, Lofes; Pravesti, Cindy Asli (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2021)
Media is part of the importance of the process of providing guidance and counseling services in schools. The media in this study was in the form of a monobiling game. Monobiling has educational value in increasing the confidence of the players (students). This study aims to determine how effective the use of monobiling game media is in increasing students' academic self-efficacy. The subjects (limited group) of this study used students of class XI who were active in SMA Negeri 15 Surabaya. This research method is in the form of development in order to produce products and product effectiveness testing. The data collection techniques in the study used interviews, media expert test instruments, and academic self-efficacy scales. Meanwhile, the data analysis used is an inter-rater agreement. Based on the results of the inter-rater agreement, it is known that the use of monobiling games to the academic self-efficacy of students in class XI at SMA Negeri 15 Surabaya is feasible and effective. This is intended to increase insight in the delivery of material regarding the academic self-efficacy of high school students. The contribution of this research is expected to optimize the game media in the implementation of guidance and counseling services